Tillage systems and their relationship with the weed flora in La Pampa province, Argentina (Semiárida, 2022)
The weed flora that develops accompanying the different agricultural production systems is exposed to the environmental filters that apply to any ecological system plus the technological components associated with crop management. Technological changes associated with an intensification of production systems have led to weed communities accompanying these transformations. The objective of the work was to characterize the weed flora according to the changes in the tillage systems and land use in the last 12 years for the agricultural area of the of the central pampas region. A bibliographic review was carried out for the 2008-2020 period, through Google Scholar tool using keywords. In addition, information from the General Directorate of Statistics and Censuses- Ministry of Production- Government of La Pampa and at the national level from the Ministry of Agriculture, Livestock and Fisheries of the Nation was also used. In Argentina, the sown area with winter and summer crops increased (7 million hectares and 29 million hectares, respectively). The relative contribution of sowed area made by the La Pampa province was maintained for the winter crops with a value of 8 %, while for the summer crops one the level of contribution of the province decreased, being 5 %. As for the La Pampa province, the area sowed with winter crops remained around 250,000 ha; the percentage made in no-till farming (SD) was increasing except for the 2019 and 2020 campaigns, reaching values of 50 % (with peaks of 65 %). The area destined to summer crops exceeded 600,000 ha during almost the entire period, except for the years 2014 and 2018; SD adoption rate was generally over 70 % (with maximum values of 85 %). The weed flora was represented by 78 species distributed in 22 families, of which the most representative were the Poaceae, Asteraceae and Brassicaceae. For summer crops, the families with the highest number of species were the Asteraceae and Poaceae represented with 11 and 14 species, respectively; 78 % were annual. For winter crops, Brassicaceae and Asteraceae were the most representative with 10 and 8 species, respectively; 81 % were annual. The weed community’s composition varied depending on the crops and the tillage system. Seventy percent of weeds that accompanied soybean, corn, and sunflower crops, and 74 % of wheat were linked to direct sowing technology. There were 38 cases of resistance to herbicides in different species for no-tillage systems, of which 34 % were for EPSPS inhibitors, and 4 for conventional tillage.
Keywords: weed communities; fine and coarse harvest; resistance; no tillage